2017
DOI: 10.1002/1873-3468.12638
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the tetramer interface of human glucose‐6‐phosphate dehydrogenase reveals kinetic differences between oligomeric states

Abstract: Glucose-6-phosphate dehydrogenase (G6PDH) catalyzes the oxidation of glucose-6-phoshate to 6-phospho-gluconolactone with the concomitant reduction of NADP to NADPH. In solution, the recombinant human G6PDH is known to be active as dimers and tetramers. To distinguish between the kinetic properties of dimers and tetramers of the G6PDH is not trivial. Steady-state kinetic experiments are often performed at low enzyme concentrations, which favor the dimeric state. The present work describes two novel human G6PDH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…The corresponding Arg residue was assessed in AoG6PDH, while, in some dual coenzyme specific enzymes the corresponding Arg residue still existed [30]. According to the crystallographic structure of dual coenzyme specific LmG6PDH, the dual coenzyme specificity was also associated with key residues surrounding conserved Arg residue and oligomeric states switching between binary and ternary enzyme complexes [15,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding Arg residue was assessed in AoG6PDH, while, in some dual coenzyme specific enzymes the corresponding Arg residue still existed [30]. According to the crystallographic structure of dual coenzyme specific LmG6PDH, the dual coenzyme specificity was also associated with key residues surrounding conserved Arg residue and oligomeric states switching between binary and ternary enzyme complexes [15,23].…”
Section: Discussionmentioning
confidence: 99%
“…1.1.1.49) is the first enzyme in the PP pathway and converts glucose-6-phosphate (G6P) to 6-phosphate-gluconolactone with concomitant generating of NADPH or NADH. In eukaryotic cells, the expression level of G6PDH is relatively constant [14,15] and it was also reported that the catalysis of G6PDH was the rate-limiting catalytic step of the PP pathway [14,16]. Accordingly, the potential for improving xylose utilization by regulation of G6PDH activity is high.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of protein oligomerization can be studied by comparing the catalytic properties of the monomeric and oligomeric enzyme forms. An approach to examine the role of quaternary structures is to artificially create the monomers by identifying putative hot spot residues in the oligomerization interface and harnessing these hot spot residues to design mutants with perturbed intersubunit interactions . In the present study, we followed a complementary approach by identifying hot spot residues in the dimer interface of known AnPRT variants by means of a comprehensive sequence comparison.…”
Section: Discussionmentioning
confidence: 99%
“…An approach to examine the role of quaternary structures is to artificially create the monomers by identifying putative hot spot residues in the oligomerization interface and harnessing these hot spot residues to design mutants with perturbed intersubunit interactions. 10,[53][54][55][56] In the present study, we followed a complementary approach by identifying hot spot residues in the dimer interface of known AnPRT variants by means of a comprehensive sequence comparison. According to the computer-based analysis (PISA service), three hydrophobic residues, I36 (numbering according to ssAnPRT) and M47 in helix α3, and I167 in helix α8, are Abbreviations: EV, elution volume obtained in analytical gel-filtration chromatography (GFC); GFC MW app , apparent molecular mass as deduced from analytical GFC; TDA MW app , weight average of samples as deduced from TDA analysis; MW calc , molecular mass calculated from the amino acid sequence for monomer or dimer; ne, not evaluable.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-6-phospahate interacted with Lys360, Asp258, Glu239, His201, His202, His263, Lys171, and Gln395 in both human and rat G6PD (Figure 2d). [35] The histidine acts as the general base that abstracts the proton from the C1-hydroxyl group of glucose 6phosphate, and the carboxylate group of Asp stabilizes the positive charge that forms on His in the transition state. In our work, we postulated that the indole derivatives could make interactions with Asp and His at active sites of the enzyme and hence block the enzymatic activity.…”
Section: Purification and In Vitro Enzyme Kinetic Studiesmentioning
confidence: 99%